Physical activity and its role in integrating people with special needs - bousskra, amer; abdsalem, Salima (sports creativity, 2025)
Human beings are integrated wholes whose intellectual, biological, psychological, and social components interact to achieve social equilibrium. Any disturbance affecting one of these components directly impacts the others, leading to a decline in the individual's ability to achieve balance on all three levels: physical, psychological, and social. In such cases, some form of care is necessary to reintegrate this group. This can also be said of people with disabilities, who are individuals who lose the ability to perform certain life activities due to physical, sensory, or intellectual impairments. These impairments may result from an accident, illness, or congenital disability. Such impairments can hinder an individual's ability to adapt to their society or environment, leading to instability and inevitably negative social consequences, such as the exclusion and marginalization of this group. In this context, the world has witnessed a fundamental shift in its ethical outlook, reflected in the emergence of organizations advocating for human rights, social justice, and equal opportunities. Our world can no longer accept the death or disability of millions of children under any circumstances. Therefore, it is essential to reintegrate people with disabilities into social life through rehabilitation and adaptation to the social environment. Among the most important forms of social care provided to people with disabilities are physical and sporting activities, which achieve psychological and social balance for each individual according to their physical and psychological abilities and aptitudes, by fulfilling their hobbies and enabling them to achieve self-realization in this and other areas. Based on the above, we will attempt to address the topic of physical and sporting activity as a form of social care and its role in reintegrating people with disabilities into social life. Accordingly, the central question of this research revolves around: Who are people with disabilities? How can physical activities contribute to achieving their psychological and social balance? And what are the most popular physical activities among this social group?